1993
DOI: 10.1002/jlac.199319930140
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Cardiovascular Activity of Stereoisomers and Derivatives of Eburnane Alkaloids

Abstract: The synthesis of all the possible isomers of the eburnameninevincamine type alkaloids l b , 2a*, 3a and derivatives 4, 8, 9, 10 is described. Structures were determined by 'H-and 13C-NMR spectroscopy including special techniques such as DR, DEPT, DNOE, and 2D-HSC. In contrast to the known cerebrovascular effects of cis-(3S,lGS) compounds, trans-(3S,lGR) derivatives show a significant peripheral vasodilator effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…[38][39][40][41] In our system, trans isomer 20 was obtained as a sole product. Comparison of the optical rotation with that reported 42) showed that the product was (Ϫ)-epieburnamonine (20).…”
mentioning
confidence: 73%
“…[38][39][40][41] In our system, trans isomer 20 was obtained as a sole product. Comparison of the optical rotation with that reported 42) showed that the product was (Ϫ)-epieburnamonine (20).…”
mentioning
confidence: 73%
“…General procedures followed during the course of the work detailed herein were similar to those reported elsewhere. 4,8 IR spectra were recorded on a Perkin Elmer Spectrum 100 FT-IR spectrometer using KBr pellets. NMR spectra were recorded on a Varian VNMRS-400 spectrometer (400 MHz for 1 H detection).…”
Section: Methodsmentioning
confidence: 99%
“…The precipitated crystals were separated, washed with water, then suspended in a mixture of EtOH/water 2:1 (110 mL) to yield 19. 4 (±)-cis-Ethyl-1-ethyl-9-methoxy-1,2,3,4,6,7,12,12b-octahydroindolo[2,3-a]quinolizine-1-(2'-hydroxyimino)-propionate (18). To 17 (6 g, 13 mmol) in EtOH (100 mL) a solution of potassium hydroxide (0.9 g, 16 mmol) in water (9 mL) was added and stirred for 3 h at 25-30 o C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it has become a reference compound in the pharmacological research of cognitive deficits caused by hypoxia and ischaemia [3]. The medicinal use of vincamine, vinpocetine, vinburnine, brovincane and further ebumane derivatives has inspired continual synthetic efforts to produce related compounds of cis-D/E ring anellation (i.e., 3a-H, 16a-ethyl: (3S, 16S) configuration), and recently, those of trans-D/E ring anellation [4,5].…”
Section: Introductionmentioning
confidence: 99%